Mode of lithospheric extension: Conceptual models from analogue modeling: - Michon, L.; Merle, O. (2003)
Comparison of analogue experiments at crustal and lithospheric scale provides essential information concerning the mode of deformation during lithospheric extension. This study shows that during extension, lithospheric deformation is controlled by the development of shear zones in the ductile parts. At lithospheric scale, the global deformation is initiated by the rupture of the brittle mantle lithosphere. This failure generates the formation of conjugate and opposite shear zones in the lower crust and the ductile mantle lithosphere. The analysis of the internal strain of the ductile layers suggests that the two opposite shear zones located below the asymmetric graben in the lower crust and the ductile mantle lithosphere prevail. Experiments show that from a similar initial stage, the relative predominance of these shear zones originates two different modes of deformation. If the crustal shear zone prevails, a major detachment-like structure crosscuts the whole lithosphere and controls its thinning. In this model named the simple shear mode, the resulting geometry shows that crustal and lithospheric thinning are laterally shifted. If the mantle shear zone predominates, the lithospheric thinning is induced by the coeval activity of the two main shear zones. This process called the necking mode leads to the vertical superposition of crustal and mantle lithospheric thinning. Applied to natural laboratories (West European rift, Red Sea rift and North Atlantic), this conceptual model allows a plausible explanation of the different geometries and evolutions described in these provinces. The North Atlantic and the Red Sea rift systems may result from a simple shear mode, whereas the necking mode may explain part of the evolution of the West European rift especially in the Massif Central and the Eger graben.